Mobility life as a new nomad - Packard, Vance (Toronto : Document Associates, 1974)
Every year one in five North Americans changes his address. Commenting on this mobility are sociologist Vance Packard, city planner Brian Ketchum, psychiatrist James Grold, and commune organizer Martin Zitter.
Converted into VHS 1/2 in. and DVD
Keywords: Occupational mobility; Residential mobility; Social mobility